Acceleration of Financial Technology Growth towards Inclusiveness of Unbankable Society in Achieving the Vision of the Islamic Banking Roadmap 2020-2025 (Case Study: Generation Z, Jabodetabek) - Ahmad Zikry Fadillah (Airlangga International Journal of Islamic Economics and Finance, 2021)
Indonesia's digital economy continues to experience positive growth. The growth of the digital economy causes the volume of digital banking transactions to continue to increase. This shows the potential in utilizing the fintech market to the fullest. However, this market has not been utilized properly because there are still unbankable people who have not been accessed by banking services. The presence of fintech is expected to be a solution to target the unbanked population. Based on the existing potential, fintech has the opportunity to be developed to increase the financial inclusion of Islamic banking in accordance with the 2020-2025 Islamic Banking Roadmap in Indonesia. With the largest Muslim population in Indonesia and through the role of Generation Z, which is a generation that grew up in the digital era, this can be a potential in increasing the role of fintech as an effort towards inclusiveness for the unbankable community. With the increase in community inclusiveness, it can encourage the acceleration of the development of Islamic banking. This study aims to optimize the role of fintech development in Islamic banking in achieving the objectives of the 2020-2025 Islamic Banking Roadmap in Indonesia. The method used in this research is quantitative research with data collection techniques through literature reviews and questionnaires. The results show that the majority of Generation Z have access to good fintech financial services. Thus, generation Z has a role in increasing the financial inclusion of Islamic banking through the use of technology services, namely fintech, so that in the end, increasingly inclusive banking finance can support the achievement of the vision of the sharia banking roadmap that has been launched by the OJK.